(untitled) (Journal of Medicine, 2010)
Poisonous snake bite is common in Bangladesh, especially on the countryside. Often fatality occurs in these cases due to lack of anti-snake venom supply in rural areas. Health professionals are sometimes found wanting in skills and knowledge in dealing with such cases. Critical care support is essential in every case of snake bite which, unfortunately, is underdeveloped in our country. We are in urgent need of locally produced anti-snake venom to ensure availability of this life-saving drug in all parts of the country. Keywords: Anti-snake venom, Bangladesh DOI:10.3329/jom.v11i1.4274 J Medicine 2010: 11: 57-59